Introduction - Hunter, Rosemary (feminists@law, 2014)
This section presents a discussion of Sarah Keenan’s book Subversive Property: Law and the Production of Spaces of Belonging (Routledge 2014). The book was launched at Birkbeck, University of London, on 12 September 2014. The three papers that follow are versions of speeches given at the launch by Davina Cooper (Professor of Law and Political Theory, University of Kent), Emma Patchett (Marie Curie Fellow, University of Münster) and Nadine El-Enany (Lecturer, Birkbeck School of Law), together with a response by Sarah Keenan (Lecturer, SOAS). The launch concluded with a musical presentation by Len Lukowski of the band FAGGOT, a link to which is also included here.